GC-MS ANALISIS TERHADAP KUALITAS MINYAK KAYU PUTIH ASAL PELITA JAYA KABUPATEN SERAM BAGIAN BARAT PROVINSI MALUKU - Jimmy Johanso Fransz; Rohny Setiawan Maail; Jimmy Titarsole (JURNAL HUTAN PULAU-PULAU KECIL, 2019)
This study was conducted to determine the Melaleuca cajuput Powell oil from Pelita Jaya Village on West of Seram Regency for more detail by using Gas Chromatography-Mass Spectrometry (GC-MS). Testing characteristics of phisycal properties was used SNI 06-3954-2001 which covers the specific of weight at 15Â°, odor, optical rotation, solubility in alcohol, fatty oil while the quality testing through chemical compounds content composition were used GC-MS. The results showed that the specific of weight requires the standard in value of 0.919, typical-green light color, there is no mixing with other oils and no fat oil with an optic rotation value of 3, 80o. GC-MS analysis proved that the quality of Melaleuca cajuput oil from Pelita Jaya village is very good with cineole content is classified as first level (P) and main (U) with a value of 60.17% and is required standard range of 24-64%.